Modelling flow-induced microstructural segregation in semi-solid metals. (January 2022) - Ma, Zhen; Zhang, Huarui; Fu, Hanwei; Fonseca, Joana; Yang, Yanzhao; Du, Ming; Zhang, Hu
Graphical abstract: Highlights: Externally solidified crystals (ESCs) migration model is proposed for flow-induced microstructural segregation. Real-time in situ X-ray synchrotron radiography of semi-solid metal flow is conducted. In-situ and validation experimental results support the ESCs migration model. The segregation is controllable by adjusting process parameters. Abstract: Lightweight alloys produced by pressurized castings suffer from flow-induced microstructural segregation due to the migration of externally solidified crystals (ESCs). Although some qualitative research has been carried out on ESCs migration, quantitative prediction of it is still demanded. In this respect, an ESCs migration model based on hydrodynamics and the rheological behaviour of semi-solid metals (SSMs) is proposed to estimate flow-induced microstructural segregation. By employing the model, a plug flow region having a decisive influence on ESCs migration is observed according to the flow simulation of yield-pseudoplastic SSMs. Good agreement between the experimental data and the simulation results is obtained, suggesting that such flow-induced microstructural segregation is controllable by manipulating process parameters such as solid fraction, cavity size and filling velocity. A real-time in situ synchrotron X-ray radiography experiment is carried out to reveal the nature of ESCs migration and provide evidence for the hypothesized flow-induced ESCs migration mechanism. A semi-empirical solid fraction-related rheological (SFR) model capable of relating rheological parameters with solid fraction of SSMs is also proposed, enabling the optimization of process parameters.